Training on Increasing the Use Value of Used Cooking Oil into Aromatherapy Candles for Bekasi Jaya Indah Housewives - Cahyaputri, Bunga; Hasibuan, Bernard (Politeknik Siber Cerdika Internasional, 2023)
There are many types of household waste. One of the wastes associated with cooking and trading activities is used cooking oil. Oil waste own impact bad for health body and environment. Therefore, that need done effort utilization oil waste become something useful for minimize waste oil waste as well as reduce pollution environment by converting into products that have added value. This is one of the goals from activity devotion this, incl increase knowledge public to impact use and disposal oil waste to health body and environment. The type of method used that is with give counseling in form socialization and description information about oil cooking. Participant looks enthusiastic with knowledge management of used cooking oil and motivate them to manage used cooking oil. Participants also add Skills in utilization oil waste become product that is candle aroma therapy as well as inspired For use it in life every day, even for help economy family.